Assessment of the Ethical Orientations of Turkish Teachers - Ozlem Ural; Soheyda Gokturk; Oguzhan Bozoglu (International Journal of Evaluation and Research in Education (IJERE), 2017)
Students’ development in terms of values, moral education and character is crucial for the culture of any society. Considering that these are gained through family and school, school principals and teachers can be the key players.  Even if teachers do not deliberately act as models or ethic agents, or their main purpose is not merely ethical education, they still affect the students directly and indirectly. Therefore, exploration of their ethical decisions and what orientations guide them in making those ethical decisions is highly important. In this regard, teachers’ ethical orientation is worth measuring. In this study, Ethical Position Questionnaire [1], which has so far been commonly used to explore ethical orientations of a variety of professionals and cultural groups was translated into Turkish; and validity and reliability study was applied on teachers. Research group consisted of 251 primary school teachers working in state schools located in Kocaeli province, Turkey. To identify the construct validity of Ethical Position Questionnaire (EPQ), factor analysis was conducted. The analysis revealed that EPQ is two factor-structured and these factors explain 45% of the variance. Cronbach’s Alpha internal consistency reliability assessed for the total items of Turkish version of EPQ was .81 and for the first subscale –idealism-, for the second scale –relativism- was found .84 and .86 respectively. In conclusion, The Turkish version of Ethical Position Questionnaire was identified as a valid and reliable research tool to assess ethical positions of primary school teachers.